Pregnancy Rate after Intrauterine Insemination with the Presence or Absence of Leukocytospermia in Sperms Prepared using Density Gradient Method - Rini Widyastuti; Julius Pangayoman; Aida Riyanti; Alkaustariyah Lubis; Mas Rizky Anggun Adipurna Syamsunarno (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To examine the association between different concentrations of leukocyte and sperm recovery rate after sperms are prepared using density gradient method and pregnancy rate after intrauterine insemination (IUI). Increased leukocytes in semen have been associated with increased reactive oxygen species (ROS) that reduces sperm quality.Methods: Semen samples that were collected from 31 male partners of couples undergoing infertility investigation were analyzed for sperm concentration, motility, and leucocytes concentration. Semen samples were then divided in two groups based on their leucocytes concentrations (category A: >0 to <1 × 106/mL; category B: >1 x 106/mL. Semen samples were processed using density-gradient centrifugation technique. Results: There was a significant difference in the number of sperms harvested and sperm motility after preparation. Interestingly, pregnancy rate after IUI was higher (p<0.05) in non-leukocytospermia semen (39%) when compared to leukocytospermia semen (30%).Conclusions: Seminal leukocytes (PMNL) concentration affects pregnancy rate after intrauterine insemination. Keywords: Density gradient method, sperm recovery rate, intrauterine insemination, pregnancy rate DOI: 10.15850/ijihs.v6n2.1318